Establishing a reference interval for serum anti-dsDNA antibody: A large Chinese Han population-based multi-center study - Deng, Chuiwen (PLoS One, 2017)
BACKGROUND: A reference interval (RI) for the circulating concentration of anti-dsDNA antibody is essential for clinicians to interpret laboratory results and make clinical decisions. Therefore, we aimed to establish the RI for anti-dsDNA antibody in the Chinese Han population. METHODS: This study was designed and carried out in accordance with guideline C28-A3, which is proposed by the International Federation of Clinical Chemistry and the Clinical and Laboratory Standards Institute. A total of 2,880 apparently healthy individuals were enrolled using a posteriori sampling. These individuals were recruited from four hospitals, representing the Han populations of north, south, east, and west China. Serum anti-dsDNA antibody levels were measured using the three analytical systems AESKU, EUROIMMUNE, and INOVA, which are the most commonly used systems in China. Individuals were stratified by gender, age, and region, and the RIs were obtained by nonparametric methods. RESULTS: Gender-specific RIs for serum anti-dsDNA antibody in the Chinese Han population were established. CONCLUSION: This is the first exploration of the RI for anti-dsDNA antibody in the Chinese Han population. We have established gender-specific RIs for each assay method commonly used in China.